Social Indifference Curves - Samuelson, Paul A. (Quarterly Journal of Economics, 1956)
I. Introduction: widespread use of community indifference curves, 1. — II. Attempts to justify the use of community indifference curves, 3. — III. Proof of the nonexistence of community indifference contours, 4. — IV. Nature of Scitovsky's community indifference contours, 6. — V. Problem of family preference: a parable, 8. — VI. Optimal ways of achieving income redistribution, 12. — VII. Regular properties of social indifference contours, 14. — VIII. Perfect competition and bliss, 19. — IX. Final summary, 21.